Enhancing maternal sleep health in Aotearoa New Zealand: insights from the Wāhi Kōrero platform - Zoe Walsh; Diane Muller; T. Leigh Signal; M. Breheny; C. Severinsen; Felicity Ware; Angelique Reweti (Kōtuitui)
Maternal sleep health is crucial for maternal wellbeing, particularly maternal mental health which has implications for the wellbeing of children, families and whānau. In Aotearoa New Zealand, the Well Child Tamariki Ora (WCTO) service provides a unique opportunity to support mothers, their families, and whānau by providing education on sleep health for both mothers and children. However, there is a need for a deeper understanding of mothers' experiences with WCTO and the sleep information they receive to enhance these services. This primary research used data gathered from the Wāhi Kōrero online story-sharing platform, with 181 stories focusing specifically on sleep. Using thematic analysis, three key themes were identified: maternal instinct as a guide in navigating child sleep practices, promoting strength-based rather than deficit-focused approaches, and the necessity to move beyond rigid, monocultural service models. Findings underscore the importance of tailoring maternal and child health services to better meet the needs and perspectives of mothers, their families, and whānau, particularly in the areas of sleep and maternal mental health. Implications of findings for future policy and practice are discussed, including developing strength-based, culturally responsive approaches within services like WCTO, and adapting policy to support more flexible, whānau-centred models of care.Glossary of Kupu Māori words: Aotearoa: Māori name of New Zealand; hapū: pregnant; kaupapa Māori: Māori ideology – a philosophical doctrine, incorporating the knowledge, skills, attitudes and values of Māori society; kōrero: to tell, say, speak, read, talk, address; Māori: Indigenous people of Aotearoa-NZ; Pākehā: New Zealander of European descent; Kāhui Rangahau: expert advisory group; wāhine: female, women; whānau: family or closely connected kin group